Impact of job burnout and work-family conflict on resilience of nurses and its influencing factor analysis (工作疲溃感与工作-家庭冲突对护士心理韧性的影响因素分析) - CAI Li (蔡莉); DONG Cuiping (董翠萍); HOU Xiaoying (侯晓营); QIAN Yan (潜艳) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the current status of job burnout, work-family conflict and resilience among nurses in the Department of Thoracic Surgery, and to analysis potential factors influencing the resilience of nurses. Methods A questionnaire-based survey using general information scale, Chinese revision of Connor-Davidson resilience scale(CD-RISC), Maslach Burnout Inventory(MBI) and Chinese revision of Work Family Conflict Inventory(WFCI) was conducted to 72 nurses. The Pearson correlation and hierarchical, stepwise multiple regression were performed for the analysis. Results There was negative relationship between resilience and job burnout (r=-0. 372, P＜0. 01)and between resilience and job burnout (r=-0. 295, P＜0. 01). Working age, number of night shifts per month, job burnout and work-family conflict were influencing factors of resilience of nurses. Conclusion Efforts should be made to develop countermeasures for relieving job burnout and work-family conflict of nurses, and improving resilience of nurses. (目的 了解胸外科护士的心理韧性、工作疲溃感及工作-家庭冲突现状, 探讨影响护士心理韧性的影响因素。方法 应用一般护士资料问卷、中文版心理韧性问卷、护士工作疲溃感问卷和工作-家庭冲突问卷对医院72名护士进行调查, 并采用Pearson相关检验和分层逐步多元回归进行分析。结果 心理韧性与工作疲溃感及工作-家庭冲突呈负相关(r=-0. 372, r=-0. 295, P＜0. 01), 影响护士心理韧性的因素为护龄、每月夜班数、工作疲溃感、工作-家庭冲突。结论 护理管理者应采取相应的积极措施降低护士工作疲溃感及工作-家庭冲突, 提高护士的心理韧性。)